Solar Coronal Heating by Kinetic Alfvén Waves - Ayaz, Syed; Li, Gang; Khan, Imran A. (The Astrophysical journal, 2024)
The utilization of the Cairns distribution serves as a vital tool for characterizing the nonthermal attributes commonly observed in space plasmas. In these intricate plasma environments, extensive measurements have been conducted to monitor the fluctuations inherent in the perturbed electromagnetic (EM) field and the associated Poynting flux, specifically concerning kinetic Alfvén waves (KAWs). Traditionally, these fluctuations have been attributed to gyroradius correction terms within the framework of Maxwellian distributed plasmas. However, our study introduces an innovative perspective grounded in kinetic theory coupled with the Cairns distribution, adept at encapsulating the nonthermal nuances characterized by the index parameter Λ. Within the domain of the solar corona, our investigation centers on the perturbed EM field ratios and the Poynting flux of KAWs, with a foundation in the Cairns distribution function. It is noteworthy that the perpendicular components, although deemed less significant due to the dominance of k ⊥ over k ∥ , remain unquantified regarding their relative insignificance. Similarly, the exploration of the imaginary part of the normalized EM field ratio has been a relatively understudied domain. Furthermore, we delve into the nuanced assessment of the power rate I x / I z characterizing the perpendicular and parallel normalized Poynting fluxes ( S x and S z ). Intriguingly, we discern that large values of Λ, compared to their Maxwellian counterparts, manifest advantageous attributes, particularly concerning the energization of the plasma over extended distances along the ambient magnetic field lines. The analytical insights gleaned from this study find practical application in understanding phenomena within the solar atmosphere, particularly shedding light on the significant role played by nonthermal particles in the observed heating processes.